Advancing kidney xenotransplantation with anesthesia and surgery - bridging preclinical and clinical frontiers challenges and prospects - Zhang, Xiaojian; Wang, Hailian; Xie, Qin; Zhang, Yang; Yang, Yixin; Yuan, Man; Cui, Yuqi; Song, Si-Yuan; Lv, Jianzhen; Wang, Yi (Frontiers in Immunology, 2024)
and surgical expertise is particularly vital, ensuring the best possible outcomes of those patients undergoing these novel transplants, through safe procedural practices. As xenotransplantation moving closer to clinical reality, establishing consensus guidelines on various aspects, including donor-recipient selection, immunosuppression, as well as surgical and anesthetic management of these transplants, is essential. Addressing these challenges through rigorous research and collective collaboration will be the key, not only to navigate the ethical, medical, and logistical complexities of introducing kidney xenotransplantation into mainstream clinical practice, but also itself marks a new era in organ transplantation.